Molecular and evolutionary insights into the structural organization of cation chloride cotransporters - Hartmann, Anna-Maria; Nothwang, Hans Gerd (Frontiers in Cellular Neuroscience, 2015)
Cation chloride cotransporters (CCC) play an essential role for neuronal chloride homeostasis. KCC2 is the principal Cl--extruder, whereas NKCC1 is the major Cl--uptake mechanism in many neurons. As a consequence, the action of the inhibitory neurotransmitters GABA and glycine strongly depend on the activity of these two transporters. Knowledge of the mechanisms involved in ion transport and regulation is thus of great importance to better understand normal and disturbed brain function. Although no overall 3-dimensional crystal structures are yet available, recent molecular and phylogenetic studies and modeling have provided new and exciting insights into structure-function relationships of cation chloride cotransporters. Here, we will summarize our current knowledge of the gross structural organization of the proteins, their functional domains, ion binding and translocation sites, and the established role of individual amino acids. A major focus will be laid on the delineation of shared and distinct organizational principles between KCC2 and NKCC1. Exploiting the richness of recently generated genome data across the tree of life, we will also explore the molecular evolution of these features.